2014
DOI: 10.4161/dish.28219
|View full text |Cite
|
Sign up to set email alerts
|

Translating research into action: An evaluation of the World Trade Center Health Registry's Treatment Referral Program

Abstract: This manuscript describes the design, implementation and evaluation of the World Trade Center (WTC) Health Registry's Treatment Referral Program (TRP), created to respond to enrollees' self-reported 9/11-related physical and mental health needs and promote the use of WTC-specific health care. In 2009-2011, the TRP conducted personalized outreach, including an individualized educational mailing and telephone follow-up to 7,518 selected enrollees who resided in New York City, did not participate in rescue/recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Despite differences in demographic characteristics, 18 prevalence of comorbidities, 53 and access to monitoring programs 54 between responders and civilians, a similar mortality risk attributed to PTSD was observed. Although previous literature has demonstrated an association between PTSD and morbidity among civilians, 5,55,56 to our knowledge, the present study is among the first to demonstrate increased mortality risk among civilians with PTSD.…”
Section: Discussionmentioning
confidence: 89%
“…Despite differences in demographic characteristics, 18 prevalence of comorbidities, 53 and access to monitoring programs 54 between responders and civilians, a similar mortality risk attributed to PTSD was observed. Although previous literature has demonstrated an association between PTSD and morbidity among civilians, 5,55,56 to our knowledge, the present study is among the first to demonstrate increased mortality risk among civilians with PTSD.…”
Section: Discussionmentioning
confidence: 89%
“…Related to this point is that we did not have CT scan data for non‐MMTP‐rescue/recovery workers. In addition, non‐MMTP rescue/recovery workers may have not enrolled in a New York‐based WTC MMTP for various reasons, including enrollment in the non‐FDNY/GRC federal WTC Nationwide Provider Network, 49 barriers related to the enrollment process, despite sustained efforts to inform them about the program, and not meeting eligibility requirements needed to enroll in a WTC MMTP 50–52 . As such, lack of data related to why they are not enrolled in a New York‐based WTC MMTP, and chest CT data in non‐MMTP rescue/recovery workers may have affected the observed findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although treatment, but not monitoring, services for certifiable 9/11‐related conditions became available after 9/11 for area residents/workers at a federally funded health program (WTC Health Program for Survivors), previous Registry studies have shown that many individuals eligible for this program had not utilized services prior to a Registry intervention, largely because they were unaware of their eligibility for this program or were not referred to the program by their primary care provider (Welch et al., , ). This emphasizes the need to train community‐based medical providers to recognize symptoms of and risk factors for PTSD and increase their knowledge and awareness of available postdisaster resources to promote timely referrals for those with current, new‐onset, or worsening PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%